Expanding and subdividing the southern and south-tropical African Kalanchoe [subg. Kalanchoe] sect. Raveta (Crassulaceae subfam. Kalanchooideae): description of K. [sect. Raveta] ser. Raveta, K. [sect. Raveta] ser. Longiflorae, and K. [sect. Raveta] ser. Rotundifoliae - Smith, Gideon F. (Phytotaxa, 2024)
Three series, Kalanchoe ser. Raveta, K. ser. Longiflorae, and K. ser. Rotundifoliae, are described in Kalanchoe [subg. Kalanchoe] sect. Raveta (Crassulaceae subfam. Kalanchooideae). The type species of all three series are indigenous to southern Africa. The first series, K. ser. Raveta, includes the robust, white-waxy kalanchoes with soup plate-sized leaves, dense-flowered, club-shaped inflorescences, and variously coloured (yellowish, whitish, greenish, and pinkish red) flowers. The second series, K. ser. Longiflorae, includes medium-sized to rather large shrubs with yellow flowers that generally do not, or hardly, show diurnal movement and do not become tightly twisted post-anthesis. The third series, K. ser. Rotundifoliae, includes small, generally low-growing, shrubby species with variously chromatic flowers (different shades of red, orange, and yellow, never white) that show distinct diurnal movement and with the flowers becoming tightly twisted post-anthesis.